Strategi Mencegah Keikutsertaan Pelajar Sekolah Menengah Atas (SMA) Pada Permainan Judi Online Di Kota Palangka Raya - Girsang, Johannes; Pane, Ronaldo; Marbun, Gracella; Lumbanraja, Aprilia Junika; Sitorus, Melati Karawangi; Jalianery, Joanita; Yestati, Ariani (Yayasan Cendekia Gagayunan Indonesia, 2025)
The development of technology and the internet has brought many changes to people's lives, especially students. With the current development of technology, digital crimes are also increasingly being committed by some irresponsible members of society. Criminal acts committed online or in the virtual world are a crime known as cyber crime. Several regulations in Indonesia govern the conduct of gambling in general, which can be found in Article 303 paragraph 1 and 303 Bis of the Criminal Code and Law No. 11 of 2008 on Information and Electronic Transactions. Although gambling has been clearly regulated, this has not made the public aware; instead, they continue to gamble. For that reason, efforts to combat online gambling require the concern of many parties, including educational institutions, especially those in the field of law. The Faculty of Law at the University of Palangka Raya has taken its role in educating the legal aspects of online gambling among students at SMA N 3 and SMA N 2 in Palangka Raya City. The research methods used are survey methods, material presentation, and the distribution of questionnaires given to the students of SMA N 3 and SMA N 2 Kota Palangka Raya.Among the roles that have been carried out are providing education through socialization methods, creating educational videos, pocketbooks, and banners. The provision of these activities has proven to be effective and capable of increasing students' knowledge about the aspects of online gambling, its dangers, and its impacts. This education cannot be conducted just once, but must be carried out continuously in order to free students from online gambling.